Subekoregije in bioregije celinskih voda Slovenije - Urbanič, Gorazd (Natura Sloveniae, 2008)
The main objective of our work was to carry out the division of inland water ecoregions - hydroecoregions of Slovenia and to define inland water subecoregions - subhydroecoregions, bioregions and large rivers. A two-stage approach was used. Initially, a division was performed using thematic maps. During the second step, a priori division was checked using biological data. Historical fish data, and benthic invertebrate data collected at reference andslightly impacted sites were used. A statistical analysis of non-metric multidimensional scaling was performed to test a priori divisions. The Alps hydroecoregion was divided in two subhydroecoregions: the Alps-Danube river basin and Alps-Adriatic river basin. The Dinarids hydroecoregion was also divided in two subhydroecoregions: the Eudinaric and Sub-Mediterranean. Hydroecoregions and subhydroecoregions were divided into 16 bioregions and 9 types of large rivers. In the Dinarids hydroecoregion, seven bioregions were defined, in the Alps hydroecoregion five bioregions, in the Pannonian lowland hydroecoregion three bioregions, whereas the Po lowland hydroecoregion was notfurther divided and has only one bioregion in Slovenia. Main abiotic differences among bioregions beside river basin are also dominant geology, maximum altitude classes and altitude classes of the influence area.
Keywords: celinske vode; Classification; Ecosystem; Ekosistem; ekosistemi; Fishes; Fresh Water; Invertebrates; Nevretenčarji; Ribe; Sladka voda; tipologija